Pelatihan Pembuatan dan Perancangan Website Sebagai Media Sosialisasi Organisasi Borneo Historical Community (BHC) di Kota Banjarmasin - Rochgiyanti, Rochgiyanti; Sriwati, Sriwati; Wafa, Itmamil; Rahmawati, Maulida (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to increase the capacity of the BHC organisation in creating and designing a website as a medium for organisational socialisation. The method of implementing this service used mentoring and training. Assistance was intended so that the BHC had socialisation media in the form of a website. In contrast, training was intended to increase the capacity of BHC administrators to manage and fill website content on an ongoing basis. The evaluation instrument for the service activities used a questionnaire via Google form and was analysed descriptively. This service indicated that the BHC, as a social organisation had social media as a means of informing the existence of the organisation to the wider community. Furthermore, the BHC management could operate the website. It was indicated by the increasing quality and quantity of content on the BHC website.